Why are filmmakers so fixated on women’s penises? an analysis of the recurrent focus on the genitalia of transgender women in film - Botha, Kellyn (My University, 2021)
Transgender women have long been misrepresented in cinema through the recurring use of representational signs which have bolstered stereotypes within the audiences who consume said cinema. The most notable of these signs is the penis, with transfeminine characters who speak openly about their genitalia, and desire to surgically remove their penises, framed as “pathetic” and comedic. Meanwhile, those who do not willingly reveal the presence of their penises, and especially those who use them, are framed as “deceptive” and often face some form of retribution by the end of the narrative. This study broadly contextualises the history of transgender cinema, analysing the ways in which the genitalia of trans women are referenced in three films released between 1970 and 2020, namely Myra Breckinridge (1970), The Crying Game (1992) and Boy Meets Girl (2014). The deconstruction of these films and critique of some existing analyses of them demonstrates a clear trend toward more holistic and sensitive representations of trans women over time, from agents of violence and abject horror, to complex human beings with diverse character traits. Also revealed, however, is that, regardless of the changes in trans representation, the penis –or genitalia, broadly –remains a recurring theme. The growth in trans activism and social acceptance of trans people, then, has not yet been able to dislodge the notion of the transgender body as an inherently sexual object, with strong ties to themes of transmedicalism, abjection, and social degradation still associated with such bodies
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts in Film and Television Studies in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2021